Perancangan Sarung Tangan Untuk Kendali Powerpoint Berbasis Wireless Menggunakan Bluetooth - Ade Ronialta; Agung Setia Budi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Technology is developing very rapidly at this time, making the human tendency to make devices that facilitate their activities. One of them is in the field of wearable devices. The Microsoft Powerpoint application is a Microsoft office application program that functions as a presentation medium where we make presentations using several slides. In this research, the author will build an embedded system that uses a flex sensor which is intended to recognize finger movements to execute commands on PowerPoint during a presentation. This wearable device uses bluetooth as a communication medium between the wearable device and a laptop or other device used for presentations. To process input and output data, use Arduino pro micro. The Arduino pro micro has an Atmega32U4 microprocessor, which allows us to add on-board USB connectivity. Flex sensors are sensors that can have a change in resistance because the sensor gets input in the form of an indentation that is applied to the sensor. The output in the form of this resistance is processed so that it can detect finger movements. The Microsoft PowerPoint application requires a device that can give commands more freely. Therefore, a wearable device was built that could give commands with the indentation of a finger. The curve received by the flex sensor will then be sent from the glove to the receiver using bluetooth communication media. There are two Arduino used respectively in gloves and receivers, the output of this device is a command to run slides in the PowerPoint application. This device can make the presentation easier.